Peranan Guru Pendidikan Agama Islam Dalam Meningkatkan Motivasi Belajar Siswa pada Pelajaran Pendidikan Agama Islam di SMP Al-Ittihad Ciampea Bogor - Ghina Habibah; Hasan Basri Tanjung; Noor Isna alfaien (Jurnal Dirosah Islamiyah, 2023)
This research is motivated by various factors that influence learning, motivation is often seen as a fairly dominant factor. Although it is recognized that intelligence and talent are the main assets in an effort to achieve academic achievement, both of them will not mean much if students as individuals do not have the motivation to achieve their best. When at school the teacher has the responsibility as a driving force in instilling motivation in students in carrying out their duties as a teacher by teaching by setting a good example. When a teacher wants to achieve his goals, it is necessary to create an environmental system by creating a more conducive learning atmosphere or conditions. Bogor. This type of research is qualitative research. The results showed that the role of Islamic religious education teachers in increasing student learning motivation in Islamic religious education lessons. Students really need motivation to participate in the learning process. The two obstacles in increasing student motivation in Islamic religious education lessons are coming from students When studying in class, they often joke , disturbing other friends and sleepy during class hours. Efforts are being made to increase student learning motivation by providing motivation, advice with a persuasive approach, looking for causes that make students undisciplined and providing solutions. Keywords: Teacher's Role, Student Learning Motivation, Islamic Religious Education.